1998
DOI: 10.1006/spmi.1996.0308
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-dependent intersubband absorption and normal-incidence infrared detection in p-type Si/SiGe quantum wells

Abstract: A detailed study of the polarization dependence of subband absorption and photoconductivity in pseudomorphic p-type Si/Si 0.64 Ge 0.36 quantum wells is presented. The fabricated quantum well infrared photodetectors (QWIP) show a photoresponse between 3 and 8 µm with a peak-wavelength of λ p = 5 µm under normal incidence illumination. At the optimum bias operating point a detectivity D * λ = 2 × 10 10 cm √ Hz W −1 is achieved. On the basis of a self-consistent six-band Luttinger-Kohn calculation the p-and s-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Here, the polarization selection rules are different because of the different symmetry of the hole wave functions in the valence band, and consequently, mid-infrared light can be absorbed under normal incidence. In recent years, there has been a growing interest in intersubband transitions of p-type SilGe quantum wells [245][246][247][248][249][250][251][252][253][254][255][256][257], making use of the mature manufacturing technology for silicon-based devices.…”
Section: Intersubband-photodetectorsmentioning
confidence: 99%
“…Here, the polarization selection rules are different because of the different symmetry of the hole wave functions in the valence band, and consequently, mid-infrared light can be absorbed under normal incidence. In recent years, there has been a growing interest in intersubband transitions of p-type SilGe quantum wells [245][246][247][248][249][250][251][252][253][254][255][256][257], making use of the mature manufacturing technology for silicon-based devices.…”
Section: Intersubband-photodetectorsmentioning
confidence: 99%
“…In addition, the epitaxial growth and processing of Si/SiGe heterostructures is compatible with Si microelectronics technology including onchip integration of SiGe focal-plane arrays with Si readout circuits. This makes strained p-type SiGe QWIPs worth pursuing [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…7 was surface normal so only xy-polarised absorption is expected for the parabolic approximation, but dependent on the samples, nonparabolicity, scattering from heterointerfaces, and scattering from the substrate can also allow a smaller amount of z-polarized transitions to be observed even in this surfacenormal geometry. 49,50 The transmission electron microscope (TEM) measurements of the narrowest Ge QW found that the samples consisted of a 5.4 6 0.4 nm Ge QW with Si 0.5 Ge 0.5 barriers all strain symmetrized to a Si 0.2 Ge 0.8 relaxed buffer. Figure 4 compares the absorption data measured in surface-normal (xy-polarized) by Fourier transform infrared (FTIR) spectrometry 7 with solutions to the present 8-band kÁp modelling.…”
Section: Mid-infrared Intersubband Optical Transitionsmentioning
confidence: 99%